Heterogeneous Hydrogenation Catalysts: Constructing the Support as a Microreactor and Regenerator for Highly Active and In Situ Regenerative Hydrogenation Catalyst (Adv. Funct. Mater. 22/2021). (26th May 2021) - Zhao, Guoqiang; Liu, Tian; Wu, Binbin; Chen, Baoliang; Chu, Chiheng
Abstract : In article number 2100971, Chiheng Chu and co‐workers introduce hierarchically ordered porous poly(2, 6‐diaminopyridine) (PDAP) as a Pd nanoparticle support for hydrogenation removal of recalcitrant pollutants in water purification. The PDAP support acts as a sorbent and microreactor to enhance the proximity of targeted water pollutants and reactive hydrogen atom species. The PDAP support also acts as a catalyst in mediating peroxide‐activation for oxidative destruction of Pd poisons.